A Research On The Technical And Financial Feasibility Of Waste Incineration Technology In Ghana - Otoo, Christopher Kwame (My University, 2023)
This research study examines the technical and financial feasibility of waste incineration technology as a solution to Ghana's growing waste management problems. The study provides an overview of the waste management situation in Ghana, highlighting the challenges associated with current waste disposal methods. The study reviews waste incineration technology, discussing its advantages, limitations, and potential application in Ghana. The study also explores the financial viability of waste incineration, analysing the costs and benefits of implementing this technology in Ghana. The study provides an overview of the financial aspects of waste incineration, including capital costs, operating expenses, and revenue potential. The study reviews the economic benefits and challenges associated with waste incineration and analyses the cost of setting up a waste incineration facility and potential revenues from energy production by applying a case study that takes into consideration all the factors that influence the successful construction and running of an energy facility in Ghana. The study also provides an overview of waste incineration technology, including its principles, processes, and equipment. The study also examines the factors that can affect the technical feasibility of waste incineration, such as the composition of waste, the type of incinerator used, and the operational conditions. The study concludes with recommendations for policymakers, waste management authorities, and investors interested in exploring waste incineration as a potential solution to Ghana's waste management challenges. Overall, this research study provides important insights into the technical and financial feasibility of waste incineration technology in Ghana, offering a valuable resource for those seeking to improve waste management practices in the country.
Keywords: waste combustion; combustion (active); treatment and handling; fi=Energiatekniikka|en=Energy Technology|; Master´s Programme in Smart Energy